Modelling the effects of ultrasonic sonification on reverse osmosis feed channel temperature - Horrigan, Liam; Freire-Gormaly, Marina (Desalination, 2022)
This paper investigates approximations of the relationship between fluid temperature and sonification within cross-flow reverse osmosis modules, as part of a broader investigation of ultrasonic fouling mitigation for small-industrial-scale reverse osmosis systems. Two discrete models approximating the temperature distributions within imperfectly thermally insulated channels subject to diffusion and axial flow were developed and compared. One model neglects the effects of temperature on diffusion while the other explicitly accounts for these effects. Neglecting temperature effects on diffusion allows for the decoupling of the mass transfer and heat transfer problems. An analytical solution to the mass transfer problem is adapted from existing literature for use in the de-coupled case. The second model accounts for the coupling effects by solving the heat and mass transfer problems concurrently. Both models require the flow properties at the channel inlet as inputs. A simulation using parameters representative of a typical small-scale industrial spiral-wound reverse osmosis module showed effectively identical temperature distribution predictions in both models, despite slight differences in their permeate flux predictions. [Display omitted] •Two models have been developed for evaluation of ultrasonic fouling mitigation in spiral-wound reverse osmosis modules.•Both models predicted slight temperature increases across module lengths, and minimal effects on membrane flux.•Future modelling will examine the effects of sonification on temperature in boundary layer regions.